Evaluation of the mechanistic basis for the antibacterial activity of ursolic acid against Staphylococcus aureus - Liu, Guanhui; Qin, Peng; Cheng, Xinying; Wu, Lifei; Zhao, Wentao; Gao, Wei (Frontiers in Microbiology, 2024)
The objective of the study was to evaluate the antibacterial efficacy of ursolic acid (UA) when used to treat Staphylococcus aureus and other isolates associated with bovine mastitis and to clarify the mechanistic basis for these effects. The bacteriostatic properties of UA extracted from Rosmarinus officinalis L. at four different purity levels were assessed by calculating minimum inhibitory concentration (MIC) values, while the synergistic effects of combining 98% UA with antibiotics were evaluated by measuring the fractional inhibitory concentration index (FICI). Changes in biofilm formation and the growth curves of the clinical isolates were assessed to clarify the bacteriostatic effect of UA. Furthermore, the cell wall integrity, protein synthesis, and reactive oxygen species (ROS) production were assessed to determine the antibacterial mechanism of UA treatment.Ultimately, UA was revealed to exhibit robust activity against Gram-positive bacteria including S. aureus (ATCC 25923), Streptococcus dysgalactiae (ATCC27957), Streptococcus agalactiae (ATCC13813), Enterococcus faecalis (ATCC29212), and Streptococcus mutans (ATCC25175). However, it did not affect Escherichia coli (ATCC 25922). The MIC values of UA preparations that were 98%, 50%, 30%, and 10% pure against S. aureus were 39, 312, 625, and 625 µg/mL, respectively, whereas the corresponding MIC for E. coli was > 5000 µg/mL. The minimum bactericidal concentrations of 98% UA when used to treat three clinical S. aureus isolates (S4, S5, and S6) were 78, 78, and 156 µg/mL, respectively. Levels of biofilm formation for clinical S. aureus isolates decreased with increasing 98% UA concentrations. Above the MIC dose, UA treatment resulted in the dissolution of bacterial cell walls and membranes, with cells becoming irregularly shaped and exhibiting markedly impaired intracellular protein synthesis. S. aureus treated with 98% UA was able to rapidly promote intracellular ROS biogenesis. Together, these data highlight the promising utility of UA as a compound that can be used together with other antibiotics for the treatment of infections caused by S. aureus.